Keanekaragaman Makrozoobentos Sebagai Bioindikator di Perairan Lentik Kawasan Rawa Jombor Klaten Jawa Tengah - Sandhie Budi Himawan; Yuni Tri Hewindati (LPPM Universitas Terbuka, 2022)
Organisms that live permanently on the bottom of lentic or still waters, such as macrozoobenthos, are very susceptible to changes in water quality that can have an impact on their composition and abundance. Because of their tolerance to environmental changes, these organisms are often used as an indicator in physical and chemical changes in the aquatic environment. Rawa Jombor or Jombor swamp is a lentic freshwater in Krakitan Village, Bayat District, Klaten, Central Java. In addition to tourism, the surrounding community uses Rawa Jombor in their daily activities for floating market and fish cages. The existence of these various activities can produce waste and garbage which then settles to the bottom of the waters and has an impact on reducing water quality. This study aims to examine the diversity and distribution of macrozoobenthos. Water quality was measured by taking samples at three locations, namely station I (littoral zone), station II (limnetic zone), and station III (benthic zone). Sampling at each station used a Van Veen grab sediment sampler. The Macrozoobenthos Diversity Index was determined using the Shannon & Wiener formula. The diversity index values for stations I, II, and III are 1.579; 1.566; and 1.785, respectively, with moderate levels of community diversity. 14 types of macrozoobenthos were identified, of which Tubifex tubifex was the most abundant species in station 1 and station 2. Meanwhile at station 3 is dominated by Anentome Helena. Based on the analysis of organism diversity and the results of water quality inspection in our study, it shows that the water quality in the Jombor swamp is classified as moderately polluted.